Finding Common Ground: A Survey of Capacitive Sensing in Human-Computer Interaction - Grosse-Puppendahl, Tobias; Holz, Christian; Cohn, Gabe; Wimmer, Raphael; Bechtold, Oskar; Hodges, Steve; Reynolds, Matthew S.; Smith, Joshua R. (Proceedings of CHI 2017, 2017)
For more than two decades, capacitive sensing has played a prominent role in human-computer interaction research. Capacitive sensing has become ubiquitous on mobile, wearable, and stationary devices—enabling fundamentally new interaction techniques on, above, and around them. The research community has also enabled human position estimation and whole-body gestural interaction in instrumented environments. However, the broad field of capacitive sensing research has become fragmented by different approaches and terminology used across the various domains. This paper strives to unify the field by advocating consistent terminology and proposing a new taxonomy to classify capacitive sensing approaches. Our extensive survey provides an analysis and review of past research and identifies challenges for future work. We aim to create a common understanding within the field of human-computer interaction, for researchers and practitioners alike, and to stimulate and facilitate future research in capacitive sensing.